Phase transformations of α-alumina made from waste aluminum via a precipitation technique - Matori, Khamirul Amin; Loy, Chee Wah; Hashim, Mansor; Ismail, Ismayadi; Mohd Zaid, Mohd Hafiz (MDPI, 2012)
We report on a recycling project in which α-Al2O3 was produced from aluminum cans because no such work has been reported in literature. Heated aluminum cans were mixed with 8.0 M of H2SO4 solution to form an Al2(SO4)3 solution. The Al2(SO4)3 salt was contained in a white semi-liquid solution with excess H2SO4; some unreacted aluminum pieces were also present. The solution was filtered and mixed with ethanol in a ratio of 2:3, to form a white solid of Al2(SO4)3·18H2O. The Al2(SO4)3·18H2O was calcined in an electrical furnace for 3 h at temperatures of 400–1400 °C. The heating and cooling rates were 10 °C /min. XRD was used to investigate the phase changes at different temperatures and XRF was used to determine the elemental composition in the alumina produced. A series of different alumina compositions, made by repeated dehydration and desulfonation of the Al2(SO4)3·18H2O, is reported. All transitional alumina phases produced at low temperatures were converted to α-Al2O3 at high temperatures. The X-ray diffraction results indicated that the α-Al2O3 phase was realized when the calcination temperature was at 1200 °C or higher.